농식품 공정거래 확립을 위한 표준거래계약서 개발 - 최병옥 (한국농촌경제연구원, 2009)
In the distribution of agricultural products, major retailers, food manufacturers and food restaurants (including collective meal service providers) exert strong bargaining power in vertical trade based on strong buying power. On top of that, they are able to sell agricultural products to consumers at low prices after buying them at lower prices from producer distributors. As the direct trade between producer distributors and retailers expands gradually thanks to changes in the environment for distributing agricultural products, there arises a need to devise measures that promote fairness and uniformity of trade by developing 'standard trade contracts' that can minimize unfair trade practices in advance. The purpose of this study was to develop three types of standard trade contracts to establish mutually cooperative fair trade between producer distributors and large retailers (including food manufacturers and collective meal service providers). Producer distributors of agricultural products wish to redress unfair contract provisions (such as those concerning the return and exchange of goods and sales grants for large purchases) that favor large retailers during when large retailers order goods directly from producer distributors for sales promotion events. As this is the case, this study conducted interviews with producer distributors and unveiled various cases of unfair trade, and thereby suggested improved provisions for standard trade contracts. This study has also found that in the case of producer distributors directly doing business with food manufacturers, producer distributors want to redress unfair contract provisions on payments, quality violation, handling of claims, and cancellation of contracts. Accordingly, this study presented various cases of food manufacturers abusing their superior position and suggested improved provisions for standard trade contracts. In the case of direct trade between producer distributors and collective meal service providers, the study has found that producer distributors wish to improve contract provisions on payments, use of distribution centers, quality violation, handling of claims, and compensation for damages. To fulfill such a need, various cases of unfair trade practices were presented and suggestions were made to improve the provisions. Meanwhile, the retailers need to continuously educate their employees so that fair trade and win-win cooperation can be firmly rooted between the suppliers and retailers. Also, they need to recognize the fact that the number of producer distributors who can continuously supply high-quality agricultural products is limited. On top of that, they should recognize that the producer distributors and retailers are not just contract parties but business partners who are engaged in business based on mutual understanding. When a producer distributor concludes a contract with a retailer, the distributor has to examine concrete provisions of the contract in advance and check whether the distributor can deliver the terms of the contract. They also need to have a good understanding of the retailer's purchasing patterns and system. Moreover, they should establish a business mind-set to supply proper goods and maintain a suitable production, processing, and distribution system to meet the quality level and quantity of goods that their partner requires. Researchers: Choi Byung-Ok and Lee Sang-Eun Research period: 2008. 11. - 2009. 1. E-mail address: bochoi@krei.re.kr